Peran Media dalam Pembeajaran di SD/MI - Suparlan Suparlan (ISLAMIKA, 2020)
Media words translated from Latinmedius that are fully translated 'middle', 'sponsored' or 'introduction. In Arabic, the media is the introduction or introduction of messages from the sender to the recipient of the message. Gerach & Ely said that the media agree here is human, material, or accident that builds needs that enable people to find out, seek or seek help. Learning is an activity or a process to gain knowledge, improve skills, improve behavior, attitudes, and strengthen personality. In the context of becoming know or the process of gaining knowledge, according to conventional scientific understanding, human contact with nature is termed experience. According to Gane, learning can determine as a process in which an organization changes its behavior as an experience.